Implementation of Governance with Transparency and Accountability in the Gunung Gambir Rubber Plantation of PTPN Nusantara 1 Regional 5 Islamic Economic Perspective - Siti Nur Fadilah (IJIEF: Indonesian Journal of Islamic Economics and Finance, 2025)
This study aims to analyze 1) how is the implementation of governance in terms of transparency? 2) how is the implementation of governance in terms of accountability? Rubber plantations are one of the strategic agricultural commodities in Indonesia, especially in East Java. One of them is the Gunung Gambir rubber plantation of PTPN Nusantara 1 Regional 5. The Gunung Gambir rubber plantation aims to increase the village's original income and stimulate the village's economy. The implementation of Good Corporate Governance (GCG) is very important for rubber plantation companies to support good governance sustainably. This research uses qualitative research with a descriptive approach, a type of approach in qualitative research using case studies. Field at the Gunung Gambir rubber plantation PTPN Nusantara 1 Regional 5. The researcher observes a phenomenon. The observation was conducted using passive participants. The validity of the data uses data source triangulation and data method triangulation, which means comparing and rechecking data obtained from different data sources. The results of this study indicate that, first, governance through transparency is closely related to the value of Siddiq in honesty, operational activities, and the dissemination of information to the public. Second, governance through accountability aligns with the value of trust, which is the primary responsibility borne by every leader and employee in financial reporting and company management.